EMPLOYEE PERFORMANCE: The Effect Of Motivation And Job Satisfaction - Andreas, Deden (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Performance is the need of all parties. For employees, performance is a way of self-preservation and well-being. As for the company, performance is an indicator of goal achievement. Therefore, performance has always been a major concern in the organization. Performance is a standardized work process and quality work, so that performance has a significant impact on the existence of the company. Departing from this phenomenon, this study is interested in analyzing employee psychological factors that are thought to have a correlation with performance. This research was conducted quantitatively with the method of statistical analysis, namely regression. The research subjects were Candika Wastu Pramathana employees. A total of 35 respondents were involved in this study, which was conducted purposively. The results of the study explain that the employee's internal factor that best explains performance is motivation. Work motivation in question is self-motivation in carrying out tasks and a sense of pleasure in many things about the organization. This attitude contributes greatly to the achievement of maximum performance.